Solitomab, an epithelial cell adhesion molecule/CD3 bispecific antibody (BiTE), is highly active against primary chemotherapy‐resistant ovarian cancer cell lines in vitro and fresh tumor cells ex vivo. Issue 3 (23rd September 2014) - English, Diana P.; Bellone, Stefania; Schwab, Carlton L.; Roque, Dana M.; Lopez, Salvatore; Bortolomai, Ileana; Cocco, Emiliano; Bonazzoli, Elena; Chatterjee, Sudeshna; Ratner, Elena; Silasi, Dan‐Arin; Azodi, Masoud; et al.
Abstract : BACKGROUND: Solitomab is a novel, bispecific, single‐chain antibody that targets epithelial cell adhesion molecule (EpCAM) on tumor cells and also contains a cluster of differentiation 3 (CD3) (T‐cell coreceptor) binding region. The authors evaluated the in vitro activity of solitomab against primary chemotherapy‐resistant epithelial ovarian carcinoma cell lines as well as malignant cells in ascites. METHODS: EpCAM expression was evaluated by flow cytometry in 5 primary ovarian cancer cell lines and in 42 fresh ovarian tumor cell cultures in ascites from patients with mainly advanced or recurrent, chemotherapy‐resistant disease. The potential activity of solitomab against EpCAM‐positive tumor cells was evaluated by flow cytometry, proliferation, and 4‐hour chromium‐release, cell‐mediated cytotoxicity assays. RESULTS: EpCAM expression was detected by flow cytometry in approximately 80% of the fresh ovarian tumors and primary ovarian tumor cell lines tested. EpCAM‐positive, chemotherapy‐resistant cell lines were identified as resistant to natural killer cell‐mediated or T‐cell–mediated killing after exposure to peripheral blood lymphocytes in 4‐hour chromium‐release assays (mean±standard error of the mean, 3.6%±0.7% of cells killed after incubation of EpCAM‐positive cell lines with control bispecific antibody). In contrast, after incubation with solitomab, EpCAM‐positive, chemotherapy‐resistant cells became highly sensitive to T‐cell cytotoxicity (mean±standard error of the mean, 28.2%±2.05% of cells killed; P <.0001) after exposure to peripheral blood lymphocytes. Ex vivo incubation of autologous tumor‐associated lymphocytes with EpCAM‐expressing malignant cells in ascites with solitomab resulted in a significant increase in T‐cell activation markers and a reduction in the number of viable ovarian tumor cells in ascites ( P <.001). CONCLUSIONS: Solitomab may represent a novel, potentially effective agent for the treatment of chemotherapy‐resistant ovarian cancers that overexpress EpCAM. Cancer 2015;121:403–412 . © 2014 American Cancer Society . Abstract : Solitomab, a novel, bispecific, single‐chain antibody, is highly active against chemotherapy‐resistant epithelial ovarian carcinoma cell lines as well as unmanipulated malignant tumor cells in ascitic fluid. Solitomab may represent a novel, potentially highly effective, targeted agent for the treatment of chemotherapy‐resistant ovarian disease that overexpresses epithelial cell adhesion molecule.